Cover Feature: Recent Progress of Two‐Dimensional Metal‐Organic Frameworks and Their Derivatives for Oxygen Evolution Electrocatalysis (ChemElectroChem 23/2020). Issue 23 (12th November 2020) - Huang, Wei; Tang, Jing; Diao, Fangyuan; Engelbrekt, Christian; Ulstrup, Jens; Xiao, Xinxin; Mølhave, Kristian
Abstract : The Cover Feature shows two‐dimensional (2D) metal‐organic frameworks (MOFs) that emerge as electrocatalysts for the oxygen evolution reaction (OER). The transition metal nodes and ligands can be feasibly adjusted for improved performance. 2D MOF derivatives are also promising. More information can be found in the Review by W. Huang et al .